Active disease and its associated factors among patients with inflammatory bowel disease in Addis Ababa, Ethiopia: a hospital-based cross-sectional study - Desalegn, Zinabu; Bane, Abate; Merdassa, Guda; Arota, Amanuel (Frontiers in Gastroenterology, 2025)
IntroductionInflammatory bowel disease (IBD) is a chronic inflammatory condition affecting the gastrointestinal tract, primarily classified into Crohn’s disease (CD) and ulcerative colitis (UC), with some cases falling into the indeterminate or unclassified category. A significant number of individuals with IBD may present with active disease, which contributes substantially to complications. Therefore, early detection of patients with clinically active disease is essential for timely referral and appropriate management to prevent related complications. This study aimed to assess the prevalence of active disease and its associated factors among patients with IBD.MethodsA hospital-based cross-sectional study was conducted at Tikur Anbessa Specialized Hospital and Adera Medical and Surgical Center, Addis Ababa, Ethiopia, in 2024. A total of 252 patients with IBD were selected using a consecutive recruitment technique. Data were collected from medical records and patient interviews using a structured questionnaire. Bivariate logistic regression was performed, followed by multivariable analysis to examine the association between the outcome and predictor variables. Variables with a p-value ≤ 0.25 in the bivariate analysis were included in the multivariable model. A p-value < 0.05 was considered statistically significant.ResultA total of 242 individuals participated in the study, yielding a response rate of 96.03%. More than one-third, 82 (33.88%), of the patients had active disease at the time of inclusion. The majority of IBD patients, 190 (78.51%), were diagnosed with CD. Patients with a monthly income between 500–1000 Ethiopian Birr (ETB) had an approximately 80% lower risk of active disease compared to those with an income of less than 500 ETB (AOR = 0.20; 95% CI: 0.05–0.79). Patients identified as being at high risk for malnutrition based on the Malnutrition Universal Screening Tool (MUST) score had about four times higher risk of active disease compared to those at low risk (AOR = 4.30; 95% CI: 1.69–10.91).ConclusionOne in every three IBD patients had active disease. MUST score and income level were found to be significant predictors of disease activity. Targeted interventions addressing nutritional, clinical, and socioeconomic determinants of IBD outcomes should be implemented.